The Influence of Consistent Social Media Communication on Brand Awareness of Ignos Studio's MSMEs - I . D. G. Aristana; I K. W. D. Prayana; N. M. Sudianti; L. P. R. A. Ratnaningrum; N. W. A. D. Pratiwi (Brilliant International Journal Of Management And Tourism, 2025)
Digital transformation has reshaped how Micro, Small, and Medium Enterprises (MSMEs) communicate with consumers, especially through social media. This study aims to examine the influence of social media communication consistency on brand awareness at Ignos Studio, a photography-based MSME using Instagram. The core issue is the lack of consistency in visual identity, verbal style, and posting frequency, which may hinder brand awareness development. A quantitative correlational survey was conducted involving 120 active followers of @ignos.studio on Instagram. Brand awareness was measured through brand recognition, recall, and top-of-mind awareness. The data were analyzed using multiple linear regression via SPSS version 31. The findings show that social media communication consistency significantly influences brand awareness (R² = 0.719). Partially, visual and frequency consistency have a significant positive effect, while verbal consistency has no significant effect. These results support the theoretical foundation of Integrated Marketing Communication (IMC), highlighting the importance of cohesive visual identity and consistent rhythm in reinforcing brand memory. This study offers practical implications for MSMEs to develop structured and consistent social media strategies to enhance sustainable brand awareness.